AI in Pharma: Accelerating Drug Development and Personalizing Healthcare - Mrs. Neha Dwivedi; Dr. Shaily Chaudhary; Udit Patidar; Vedant Vyas; Sumit Varfa; Solu Goyal; Sourabh Patel; Akash Yadav (Revista Electronica de Veterinaria, 2024)
Artificial Intelligence (AI) and machine learning are useful in drug discovery, pharmaceutical formulation and dosage form testing. By analyzing biological data like preteomics and genomics. Researchers can indentify disease related target and predicts how they will interact with treatment. AI is rapidly becoming a powerful tool that help solve complex problems more quickly and efficiently. This improve drug approval success and helps focus drug research efforts. AI also lower the process and expense of development. The pharmacokinetics and toxicity of possible drugs are predicted by machine learning algorithms, which also aid in study design. Artificial Intelligence ( AI ) systems evaluate real patients data and assists with medical plan to improve treatment results. AI and drug discovery have many uses including design, testing, and pharmacokinetics and pharmacodynamic analysis. The ongoing research into AI by the pharmaceutical industry today presents numerous chances to improve patient care and the medication development process.